1997
DOI: 10.1155/dte.5.19
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transhepatic Cholecystoscopic Lithotomy in the Management of Acute Cholecystitis Caused by Gallbladder Stones

Abstract: Percutaneous transhepatic cholecystic drainage (PTCCD) with percutaneous transhepatic cholecystoscopic lithotomy (PTCCSL) were performed in 53 patients with acute cholecystitis caused by gallbladder stones and studied stone removal rates, complications, endoscopic findings, and stone recurrence. The stones were successfully removed in 96% of the patients, and there were no serious complications. The coexistence of cancer was confirmed in three patients, and all cases were accurately diagnosed on the basis of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…While useful in smaller stones, unfortunately, fluoroscopic percutaneous extraction is limited by stone size. With the advent of cholecystolithotripsy, Picus et al ., in 1992, reported their experience with percutaneous cholecystoscopy and electrohydraulic lithotripsy in 58 high‐risk patients with acute cholecystitis or biliary colic, adopting similar techniques described previously by surgeons and gastroenterologists . Complete stone removal was achieved in 97% over a mean of 1.6 sessions, with major and minor complication rates of 9% and 3% respectively .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While useful in smaller stones, unfortunately, fluoroscopic percutaneous extraction is limited by stone size. With the advent of cholecystolithotripsy, Picus et al ., in 1992, reported their experience with percutaneous cholecystoscopy and electrohydraulic lithotripsy in 58 high‐risk patients with acute cholecystitis or biliary colic, adopting similar techniques described previously by surgeons and gastroenterologists . Complete stone removal was achieved in 97% over a mean of 1.6 sessions, with major and minor complication rates of 9% and 3% respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by non‐Interventional Radiology groups have reported comparable outcomes using similar techniques. Ohashi et al., in 1998, reported a 96% technical success rate (mean sessions: 2.5) in 53 average‐risk patients with acute cholecystitis. Complications occurred in 4%, and recurrent calculous cholecystitis occurred in 2.5% (mean follow‐up: 42 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5, 6 We performed percutaneous endoscopic cholecystolithotomy to remove difficult, impacted cystic duct stones with complete gallbladder clearance. Because retrograde cannulation was not possible even after precut papillotomy, an internal rendezvous through the gallbladder allowed successful ERCP with clearance of choledocholithiasis.…”
Section: Discussionmentioning
confidence: 99%